Description of Incompleteness of Prescription Writing at Surabaya Islamic Hospital A. Yani - A’yun Faradinna, Riskylah; Setianto, Budhi (Rifa'Institute, 2023)
Introduction: Medication error is an event that harms patients due to incorrect use of drugs during the treatment of health workers. Medication error can lead to increased mortality or mortality, increased duration of hospitalization, and increased cost of treatment. Objective: This study aims to provide an overview of efforts to reduce the incompleteness of prescription writing at Surabaya Islamic Hospital A. Yani in each of its parts, namely inscription, invocation, precriptio, subcribtio, and pro. Method: The type of research used is qualitative case studies and secondary data analysis of patient safety incompleteness of prescription filling at Surabaya A. Yani Islamic Hospital. Data collection by observation and interview. Result and Discussion: The results showed that efforts to reduce the incompleteness of prescriptions carried out by Surabaya A. Yani Islamic Hospital using the E-prescription system. It is hoped that the existence of E-prescription can reduce the occurrence of human error and make it easier for doctors and pharmacists to provide services. Conclusion: The conclusion of this study is that the doctor's identity and the date of writing the prescription in the inscription section, the dose of the drug in the precriptio section, the doctor's paraphrase in the subcriptio section and the patient's weight in the pro section. E-prescriptions are used as an upgrade system to replace manual prescriptions. Evaluation and socialization are carried out as an effort to reduce the number of incompleteness of writing recipes